Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Petugas Pemadam Kebakaran di Suku Dinas Pemadam Kebakaran dan Penyelamatan Jakarta Selatan - Apriliani Apriliani; Ony Linda; Nurul Huriah Astuti (UHAMKA Press, 2019)
ABSTRACT Fire cases during 2017 experienced an increase from the previous year, therefore many firefighters experienced fatigue. This study aims to determine the level of fatigue experienced by officers and to find out related factors associated with work fatigue. This is quantitative research with cross sectional study design with technique total sampling as much 61 person. Data collection is done by interview and direct measurement. Analysis of univariate data show that 83,6% respondents are aged, 62,3% respondents normal nutritional status, 82% respondents year of service old, 54,1% respondents not enough sleep duration, 54,1% respondent with not good work time, 52,5% respondent with smoking status and 83,6% do not have history of disease. Based of statistical test use person chi square the results show that there was a relation between age (p value = 0,018), year of service (p value = 0,009), sleep duration (p value = 0,028), work time (p value = 0,028), smoking status (p value = 0,015), with work fatigue at firefighters and rescue services offices in South Jakarta Year 2018. Efforts are needed to eliminate or reduce work fatigue at firefighters by providing adequate rest periods and dividing tasks in accordance with the age and working period of the officers, and can provide counseling and installation of posters about the dangers of smoking. Keyword : Fatigue, Risk Factors, Firefighter